Nathan Yost. Fall of Communism in Hungary - Yost, Nathan (Young Scholars Grinchenko – Seton International Journal, 2022)
In 1956, Hungary’s communist leadership, under Imre Nagy, attempted to introduce multi-party elections and remove Hungary from the Soviet sphere of influence. This move did not go over well with the Soviets. They quickly removed Nagy from power, replacing him with hardliner Janos Kadar. Kadar was able to maintain a stable communist regime for more than 3 decades, until 1988. After Soviet reformer Mikhail Gorbachev’s rise to power, reform-minded communists in Hungary became increasingly prominent. In 1989, they succeeded in organizing a National roundtable with opposition groups within Hungary and free elections were held in late 1989. Hungary’s communists were handily defeated. 1990 officially marked the end of communism as Jozsef Antall took power as the first non-communist leader in Hungary in over 40 years.